Search for Branons at LEP - Achard, P. (2004)
We search, in the context of extra-dimension scenarios, for the possible existence of brane fluctuations, called branons. Events with a single photon or a single Z-boson and missing energy and momentum collected with the L3 detector in e+e− collisions at centre-of-mass energies √2 = 189–209 GeV are analysed. No excess over the Standard Model expectations is found and a lower limit at 95% confidence level of 103 GeV is derived for the mass of branons, for a scenario with small brane tensions. Alternatively, under the assumption of a light branon, brane tensions below 180 GeV are excluded.